A comparative analysis of microplastic contamination in hermit crab Clibanarius rhabdodactylus Forest, 1953, inhabiting intertidal and subtidal Coastal habitat of Gujarat state - Jaimin Parmar; Krupal Patel; Vasantkumar Rabari; Ashish Patel; Dipak Kumar Sahoo; Jigneshkumar N. Trivedi (PLoS ONE, 2025)
Microplastics (MPs) contamination has increased significantly due to inadequate plastic waste, leading to MPs infiltration in marine organisms. Crustaceans, especially the anomuran crabs, represented significant benthic communities in the intertidal zone. The current investigation aims to check the variation in MP contamination in Hermit crab Clibanarius rhabdodactylus inhabiting the intertidal and subtidal zone of Gujarat state, India. A total of 50 crabs (25 males and 25 females) of C. rhabdodactylus were collected from both zones along the coast of Gujarat in January and February 2024. In the laboratory, hermit crabs were weighed, dissected, and processed for tissue digestion. Sediment and water samples also underwent digestion. All samples were then processed through flotation, filtration, microscopic observation, and chemical characterization. The higher contamination was recorded in intertidal specimens than in subtidal specimens. The MP contamination in C. rhabdodactylus varied significantly between intertidal and subtidal specimens. MP contamination in both habitats was greater in females than in males. MP contamination in sediment and water was higher in the intertidal region than in the subtidal region, with no significant difference. Morphometric examination of MPs indicated the maximum abundance of fibers in terms of MP shape, followed by fragments and films. Black coloured MPs with 0.5–1 mm size were recorded dominantly in both habitats. The isolated MPs were primarily composed of polyethylene and polypropylene polymers. This study proposed immediate measures to address the issue of effective management of plastic litter in the marine ecosystem of the state. The present study revealed that MPs are widely distributed in the intertidal region and possess a greater risk of MP accumulation than those in the subtidal region.